2004
DOI: 10.1016/j.ejvs.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cell Apoptosis in Primary Varicose Veins

Abstract: P53-related apoptosis is one of the regulatory mechanisms of vein wall homeostasis maintenance. During varicose vein development its activation is related to the early stages of the disease. In the further course, the down-regulation of the SMC apoptosis within the vein media leads to the structural changes increase. The reduction of the SMC population corresponding to an increase of p21 expression in proximal saphenous vein segments suggests that the cell cycle disturbances may lead to the 'weakness' of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 46 publications
1
36
1
6
Order By: Relevance
“…The immunoreactivity was stronger in older patients and in females [81]. The importance of apoptosis and cell cycle regulation in the development of VVs may be confirmed by the overexpression of p53, p21, BCL-2 and BAX, which role in programmed cell death is widely known [39,[82][83].…”
Section: Other Factors Associated With Varicose Veinsmentioning
confidence: 84%
“…The immunoreactivity was stronger in older patients and in females [81]. The importance of apoptosis and cell cycle regulation in the development of VVs may be confirmed by the overexpression of p53, p21, BCL-2 and BAX, which role in programmed cell death is widely known [39,[82][83].…”
Section: Other Factors Associated With Varicose Veinsmentioning
confidence: 84%
“…A previous study has demonstrated that MGP regulated apoptosis at different stages of cell differentiation [57]. Decreased apoptosis in the medial layer of varicose veins has been described [59, 60]. Involvement of MGP in the decreased programmed varicose cell death will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the differentiation of VSMCs has been implicated in various vascular pathologies, including atherosclerosis, 6,7 intimal hyperplasia, 8,9 and varicose vein formation. [10][11][12][13][14] Several studies have described phenotypic alterations of VSMCs in varicose veins. [10][11][12][13][14] Specifically, it has been reported that VSMCs isolated from varicose veins exhibit phenotypic transformation from a contractile to a synthetic state.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] Specifically, it has been reported that VSMCs isolated from varicose veins exhibit phenotypic transformation from a contractile to a synthetic state. [10][11][12][13][14] Electron microscopic analysis of these cells further revealed that they were poorly differentiated, with an increased presence of secretory cytoplasmic organelles (suggesting unusual synthetic and secretory roles for these VSMCs) and a reduction in filament bundles (implying decreased contractile capability). 10 It is well established that there is a genetic component to the formation of varicose veins.…”
mentioning
confidence: 99%